Performance assessment of 11 commercial serological tests for SARS-CoV-2 on hospitalised COVID-19 patients. (March 2021) - Serre-Miranda, C.; Nobrega, C.; Roque, S.; Canto-Gomes, J.; Silva, C.S.; Vieira, N.; Barreira-Silva, P.; Alves-Peixoto, P.; Cotter, J.; Reis, A.; Formigo, M.; Sarmento, H.; et al.
Highlights: Sensitivity heterogeneity of severe acute respiratory syndrome coronavirus-2 serological tests. Maximum sensitivity achieved 21 days from symptoms onset. COVID-19 clinical outcome is associated with different immunoglobulins levels. Abstract: Background: Commercial availability of serological tests to evaluate immunoglobulins (Ig) targeting severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has grown exponentially since the start of the coronavirus disease 2019 (COVID-19) outbreak. Thorough validation of these tests is important before use as epidemiological tools to infer seroprevalence in specific populations and as diagnostic tools to complement molecular approaches (e.g., quantitative reverse transcription-polymerase chain reaction). Methods: Commercial serological tests from 11 suppliers were assayed side-by-side using 126 samples from SARS-CoV-2-infected inpatients and 36 from healthy and HIV-infected individuals. Results: The majority of the tests assayed have >95% specificity. For the sensitivity calculation, samples were stratified by days since symptoms onset; sensitivity peaks at 16–21 days for IgM and IgA (maximum 91.2%, Euroimmun) and, dependant on the test, at 16–21 or >21 days for IgG (maximum 94.1%, Snibe). Data from semiquantitative tests show that patients with a severe clinical presentation have lower levels of Ig targeting SARS-CoV-2 at <10 days since symptoms onset and higher levels at >21 days, compared to patients with a non-severe presentation. Conclusions: This study highlights the heterogeneity of sensitivity and generally high specificity of the serological tests and establishes a basis for their usefulness to complement diagnostic techniques and population seroprevalence studies.